Annual Plan 1994-95 Volume-VIII V Energy, VI Industry and Minerals Hill Areas Government of Assam - Planning Commission (Planning Commission, 1994)
There are 1,931 Nos. of census villages as per 1971 census in the two Hill Districts of Assam. 1,119 Nos. of census villages already electrified upto 31-3-93. Moreover, 109 Nos. of non-census villages were also electrified upto 31-3-93. The outlay against Rural Electrification during 1993-94 is Rs.200.00 lakhs. It is envisaged to electrify 6 Nos. of new villages in the two Hill Districts of Assam during this year. An amount of Rs.30.00 lakhs has been proposed during 1994-95. It is envisaged to electrify 3 Nos. of villages.
Government of Assam